IRRI: Stress tolerant for Africa and South Asia (Phase 2) - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: This project developed a standardized data collection procedure to make women’s participation in rice cultivation visible. There is a need to reduce the gap between men and women in terms of access to technologies, technical knowledge and capacity enhancing programs. Research on family cultivation among the rural poor, acknowledges women as farmers. Though discriminated against, on closer examination they are active participants in breeding, cultivation and harvesting. IRRI is interested in shifting research from yield to market-oriented breeding but there is a need to better understand the demand-side context – what types of varieties and qualities are valued. Knowledge and technologies that influence livelihood progress typically go to landowners – men. The goal is to use aggregated data that quantify female labour contributions to demonstrate to rice breeding researchers the ways women both influence and are influenced by technologies within the rice production system. The emphasis is on how to ensure women farmers have access to technologies that both increase livelihoods and capacity and productivity in the broader rice production system. For instance, women who take care of livestock prefer varieties with long stock for quality animal fodder. At the household scale women want varieties that can cook faster and remain softer throughout the day in order to reduce overall time spent cooking in order to focus on other activities.